Lower serum levels of alpha tocopherol and lycopene is associated with higher pain and physical disability in subjects with primary knee osteoarthritis: A case-control study - Eftekharsadat, Bina; Aghamohammadi, Dawood; Dolatkhah, Neda; Hashemian, Maryam; Salami, Halale (International journal for vitamin and nutrition research, 2021)
: We aimed to determine dietary intake and serum concentration of α-tocopherol and lycopene in subjects with knee osteoarthritis (KOA) in relation to pain intensity and functional status and comparing them with healthy controls. : This case-control study was conducted among 35 patients with primary KOA and 35 matched healthy subjects selected using convenience sampling method. Dietary intakes of alpha-tocopherol and lycopene were estimated from 24-hour dietary records. Visual Analogue Scale (VAS) and Western Ontario and McMaster (WOMAC) index were used to assess the pain and functional status, respectively. : Serum concentrations of alpha-tocopherol ( = ) and lycopene ( = ) were significantly lower in OA patients in comparison with healthy controls. Dietary intake of alpha-tocopherol was negatively associated with total WOMAC score ( = = ) and pain ( = = ) and physical function ( = = ) subscales. Dietary intake of lycopene was negatively associated with total WOMAC score ( = < ) and pain ( = = ) and physical function ( = < ) subscales. Additionally, serum concentration of alpha-tocopherol was negatively associated with total WOMAC score ( = < ) and physical function subscale ( = < ). Serum concentration of lycopene was negatively associated with total WOMAC score ( = = ) and physical function subscale ( = = ) : Serum concentrations of α-tocopherol and lycopene were significantly lower in patients with KOA than in healthy controls. Significant negative association was detected between serum concentration and dietary intake of α-tocopherol and lycopene with functional disability in patients with KOA.